Getting the basic nature of systemic corruption right: A reply to Marquette and Peiffer. Issue 4 (28th March 2019) - Persson, Anna; Rothstein, Bo; Teorell, Jan
Abstract : In reply to Marquette and Peiffer's article "Grappling With the 'Real Politics' of Systemic Corruption: Theoretical Debates Versus 'Real‐World' Functions, " this article employs three criticisms: Marquette and Peiffer's call to grapple with the "real politics of corruption" does not bring much new to the table, is conceptually flawed, and risks serving as an excuse for corrupt elites to pursue "business as usual." In response, we reaffirm three insights gained from collective action‐based approaches toward corruption. Although corruption might solve individual‐level problems in the short term, it is still a de facto problem at the aggregate level, the tools derived from principal–agent theory will not solve the collective action problem of systemic corruption, and elites will be the least likely to implement reform. We conclude by calling for the continued fight against corruption—a fight informed by empirical and theoretical knowledge.